THE EFFECT OF PRODUCT QUALITY AND PRICE ON PURCHASING DECISIONS FOR WARDAH COSMETICS AT BRASTAGI SUPERMARKET CEMARA, MEDAN CITY - Syafiyyah Amaliyyah Nasution; ASRINDAH Nasution; Sri Mulyani (Universitas Dharmawangsa Medan, 2026)
This study aims to determine the influence of product quality and price on purchasing decisions for Wardah cosmetics at Brastagi Supermarket Cemara in Medan City. The background of this study is based on the importance of understanding the factors that influence consumer purchasing decisions, particularly in the increasingly competitive cosmetics industry. The independent variables in this study are product quality and price, while the dependent variable is the purchase decision. The research method used was a quantitative method with an associative approach. Data collection was conducted through questionnaires distributed to consumers who had purchased Wardah cosmetics at Brastagi Supermarket Cemara in Medan City. Data analysis techniques used included validity testing, reliability testing, classical assumption testing, multiple linear regression analysis, t-tests, F-tests, and the coefficient of determination (R-square). The results showed that product quality partially had a positive and significant effect on purchasing decisions, and price also had a positive and significant effect on purchasing decisions. Furthermore, product quality and price simultaneously had a significant effect on purchasing decisions. Price was the most dominant factor influencing purchasing decisions. The coefficient of determination (R Square) of 0.644 indicates that 64.4% of purchasing decisions can be explained by product quality and price, while the remaining 35.6% is influenced by other variables outside the study. Based on the research results, it is recommended that companies continue to improve product quality and maintain competitive pricing strategies to increase consumer purchasing decisions.